Deaf translators in audiovisual media: The case of an inclusive and co-creative laboratory in Uruguay - Tancredi, Marcela; Lorier, Leticia; Boria, Yanina; Fascioli-Alvarez, Florencia (The Journal of Specialised Translation, 2023)
Accessibility is a necessary condition for the exercise of rights (Greco 2016). When it comes to the deaf linguistic community (Peluso 2010), contexts are more accessible if sign language (SL) is present. The participation of members of this community in translation and interpretation processes and their presence on camera in audiovisual productions are also considered necessary. The way of working described in this article is designed to improve accessibility by not only including minorities (such as deaf sign language users) in the traditional place of validation, but also by giving them a much more relevant and innovative role in the whole process and ultimately making them an essential part of the team of media accessibility (MA) professionals. Our case study focuses on a university experience, showing a way for deaf translators to work in audiovisual media. The aim is to give an account of MA co-creation with deaf people.